mRNA and miRNA expression profile reveals the role of miR-31 overexpression in neural stem cell - Li, Pengfei (Sci Rep, 2020)
A detailed understanding of the character and differentiation mechanism of neural stem cells (NSCs) will help us to effectively utilize their transplantation to treat spinal cord injury. In previous studies, we found that compared with motor neurons (MNs), miR-31 was significantly high-expressed in NSCs and might play an important role in the proliferation of NSCs and the differentiation into MNs. To better understand the role of miR-31, we characterized the mRNA and miRNAs expression profiles in the early stage of spinal cord-derived NSCs after miR-31 overexpression. There were 35 mRNAs and 190 miRNAs differentially expressed between the miR-31 overexpression group and the control group. Compared with the control group, both the up-regulated mRNAs and miRNAs were associated with the stemness maintenance of NSCs and inhibited their differentiation, especially to MNs, whereas the down-regulated had the opposite effect. Further analysis of the inhibition of miR-31 in NSCs showed that interfering with miR-31 could increase the expression of MNs-related genes and produce MNs-like cells. All these indicated that miR-31 is a stemness maintenance gene of NSCs and has a negative regulatory role in the differentiation of NSCs into MNs. This study deepens our understanding of the role of miR-31 in NSCs, provides an effective candidate target for effectively inducing the differentiation of NSCs into MNs, and lays a foundation for the effective application of NSCs in clinic.